Glutamine metabolism in cancers: Targeting the oxidative homeostasis - Gong, Tengfang; Zheng, Changbing; Ou, Xidan; Zheng, Jie; Yu, Jiayi; Chen, Shuyu; Duan, Yehui; Liu, Wei (Frontiers in Oncology, 2022)
Glutamine is the most abundant amino acid in blood and tissues, and the most important nutrient except for glucose in cancer cells. Over the past years, most of studies focus on the role of Gln metabolism in supporting energy metabolism rather than maintaining oxidative homeostasis. In fact, Gln is an important factor in maintaining oxidative homeostasis of cancer cells, especially in “Glutamine addicted” cancer cells. Here, this paper will review the recent scientific literature about the link with Gln metabolism and oxidative homeostasis, with an emphasis on the potential role of Gln metabolism in different cancers. Given that oxidative homeostasis is of critical importance in cancer, understanding the impacts of a Gln metabolism on oxidative homeostasis, gaining great insights into underlying molecular mechanisms, and developing effective therapeutic strategies are of great importance.